Catholic Priesthood’s Proper Matter: A Female Presbyterate? - Del Rio, Carlos M (Advances in Social Sciences Research Journal, 2015)
Conflating human gender and human sexual identity leads to fallacious conclusions that lack ontological corroborations. The Latin Rite of the Roman Catholic Church’s preference for an all “men-male” celibate priesthood shares this preponderant conflation. An examination of gender and sexuality evinces denotative distinctions among these human dimensions and deconstructs the Church’s conflation that seeks for a fitting priestly representation of Jesus’ maleness (sexual identity). Doubtless not all ordained men are males, but all ordained males are men, some of whom (men and males) remain sexually active. This de facto reality also deconstructs a “celibate” priesthood, rendering celibacy’s inception only a disciplinary legislation. Furthermore, an Aristotelian examination of sacraments demonstrates the human person regardless of gender or of sexual identity is the proper matter for sacred orders. This makes the case for a female presbyterate.